2018
DOI: 10.1039/c7ra11420f
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative pharmacokinetics of four active components on normal and diabetic rats after oral administration of Gandi capsules

Abstract: The Gandi capsule, a famous traditional Chinese medicine (TCM), is a hospital preparation that has been widely used in China for decades for the treatment of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The P app values determined in the present study indicated good intestinal absorption of loganin. At first instance this high permeability observed in the Caco-2 model seems to be inconsistent with the previously reported low oral bioavailability of loganin [11]. Besides its low water solubility, a strong metabolism may be regarded as the major cause of the low oral bioavailability of loganin in vivo.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The P app values determined in the present study indicated good intestinal absorption of loganin. At first instance this high permeability observed in the Caco-2 model seems to be inconsistent with the previously reported low oral bioavailability of loganin [11]. Besides its low water solubility, a strong metabolism may be regarded as the major cause of the low oral bioavailability of loganin in vivo.…”
Section: Resultsmentioning
confidence: 57%
“…Chromatographic and mass spectrometry detection were performed according to a previous method [11]. Briefly, loganin and puerarin (internal standard, IS) were isolated using a ZORBAX Eclipse Plus C 18 column (50 mm × 2.1 mm, 1.8 μ m) with an API5500 triple-quadrupole mass spectrometer (Applied Biosystems-SCIEX, Concord, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure of baicalin and also of wogonin and wogonoside was significantly higher in diabetic rats (models induced with streptozotocin) than in healthy rats, and this seemed to be related not to an increase of absorption (the intestinal permeability for baicalin rather decreased), but to an increase in the activity of β-glucuronidase [270,271,272,273,274,275]; a delay in gastric emptying and thus prolongation of the mean residence time in the gastro-intestinal tract of the flavones was also suggested as possibly contributing to this increase in exposure in diabetic animals [275]. A similar effect was also reported in diabetic mice (model of diabetes used in the experiment not reported), the sample of which also contained oroxylin A and baicalin (unlike the non-diabetic mice used as a control) [276].…”
Section: Intra-species Differences (Pk Variability)mentioning
confidence: 99%
“…Furthermore, most studies concentrated on the pharmacokinetic characteristics of DZXXI under normal states [18,19]. However, the pharmacokinetic behavior of the TCM under pathological state may differ from that of normal status [20][21][22][23][24]. Besides, numerous studies have shown that the pharmacokinetics features of TCM are affected under the condition of disease [25][26][27].…”
Section: Introductionmentioning
confidence: 99%